Pendidikan Multikultural: Upaya Membangun Keberagamaan Inklusif di Sekolah - Husniyatus Salamah Zainiyati (Islamica: Jurnal Studi Keislaman, 2007)
Indonesia, with its diverse social, cultural and geographical variety, is one ofthe biggest multicultural societies in the world. This diversity ?when misused- can causemany problems such as corruption, collusion, nepotism, poverty, violence, damage toenvironment, separatism, and human right violation. Vis-?-vis this, multicultural educationsuggests that diversity of ethnicity, culture, language, religion, society, gender, intellectualacumen and age can in fact be used to create inclusive pluralism through sufficientstrategy and efficient concept of education. In practical terms, what is required from ateacher in this whole concept of education is not only to be able to teach his/her subjectmatter, but also to implant the multicultural and inclusive values such as democracy,humanism, and pluralism. In the end, what this approach can achieve is to produce theout-put that has not only the academic skill in his/her specialization, but also the ability toadopt and apply the norms of pluralism which will lead him/her to be more tolerant andunderstanding toward diversity and differences.